Immune Cell Plasticity Allows for Resetting of Phenotype From Effector to Regulator With Combined Inhibition of Notch/eIF5A Pathways - Imam, Shahnawaz; Dar, Pervaiz; Aziz, Saba Wasim; Zahid, Zeeshan A.; Sarwar, Haider; Karim, Tamanna; Faisal, Sarah; Haseeb, Ibrahim; Naqvi, Ahmed S.; Shah, Rayyan; Haque, Amna; Salim, Nancy; et al. (Frontiers in Cell and Developmental Biology, 2021)
Type 1 diabetes (T1D) results from the destruction of pancreatic β-cells caused by an altered immune balance in the pancreatic microenvironment. In humans as well as in mouse models, T cells are well recognized as key orchestrators of T1D; which is characterized by T helper (Th) 1 and Th17 cell bias and/or low/defective T-regulatory cells (Treg), that culminates into cytotoxic T-cell (CTL) mediated destruction of β-cells. Refitting of immune cells towards non-inflammatory phenotype in the pancreas may represent a way to prevent/treat T1D. Recently we have developed a unique spontaneous humanized mouse model of Type 1 Diabetes, wherein mouse MHC-II have been replaced by human DQ8 and β-cells were made to express human Glutamic Acid Decarboxylase (GAD) 65 auto-antigen. The mice spontaneously developed T1D resembling the human disease. Humanized T1D mice show hyperglycemic (250-300mg/dl) symptoms by the 4th week of life. The diabetogenic T cells (CD4, CD8) present in our model are GAD65 antigen specific in nature. Intermolecular Antigen Spreading recorded during 3rd-6th week of age is like that observed in human preclinical period of T1D. In this paper, we tested our hypothesis in our spontaneous humanized T1D mouse model. We targeted two cell-signaling pathways and their inhibitions: eIF5A pathway inhibition influences T helper cell dynamics towards non-inflammatory phenotype and Notch signaling inhibition enrich Tregs and targets auto-reactive CTLs, rescues the pancreatic islet structure and increases the functionality of β-cells in terms of insulin production. We report that inhibition of (eIF5A+Notch) signaling mediates suppression of diabetogenic T cells by inducing plasticity in CD4+ T cells co-expressing IL17 and IFNγ (IL17+IFNγ+) towards Treg cells phenotype.